Nutritional Experiment in Sand Culture of Acacia auriculaeformis. (benth.) A. Cunn - Banerjee, A. K. (Indian Forester, 1973)
A Sand culture nutritional experiment of Acacia auriculaeformis was done in the Glass House at Midnapore in 1972. Results have shown that the species respond significantly to NH4NO3 and K2SO4 application. P does not seem to have any significant effect. The linear components of interaction of NH4NO3 and K2SO4 are also significant at 1% level.